Multiplikasi Tunas dan Induksi Perakaran pada Ubi Kelapa (Dioscorea alata L.) dan Gembili (Dioscorea esculenta L.) Secara In Vitro - Hutami, Sri; Purnamaningsih, Ragapadmi; Mariska, Ika; Diantina, Surya (Jurnal AgroBiogen, 2014)
Dioscorea sp. (yam) is one of the minor tuber crops whichgrows wildly in the forest and only a few of its species arecultivated and used as main or secondary food.Conservation is needed to preserve plant genetic material.The objective of this research was to obtain methods ofplantlets propagation of D. alata L. and D. esculenta L.through in vitro culture. The research was conducted atTissue Culture Laboratory of ICABIOGRAD in 2012. Theresearch consisted of three stages. First, shoot emergence.In this experiment, young shoots were planted in MS basicmedium combined with benzyl adenine (BA) (0, 1, 3, and 5mg/l) and gibberelic acid (GA) (0 and 5 mg/l). Second, shootmultiplication. Shoots of Dioscorea which were planted inthe best medium of the first experiment were subcultured inMS medium combined with thidiazuron (0, 0.1, 0.5, 1, 2, and3 mg/l). Third, root initiation. Shoots of Dioscorea whichwere planted in the best medium of the second experimentwere subcultured in MS medium (Â½ MS and 1 MS)combined with indole-3-butyric acid (IBA) (0, 1, 3, and 5mg/l). Result of these experiments showed that shootemergence of D. alata L. and D. esculenta L. began at 2weeks after planting in MS medium. More plantlets of D.alata L. and D. esculenta L. were obtained by shootmultiplication in MS media. Root initiation of the Dioscoreabegan at 4 weeks after planting in MS media. The addition ofIBA (3â€“5 mg/l) on D. esculenta L. could not stimulate rootingbut led to the formation of callus at the base of the stembuds.